OVIAN DECAMETER RADIO EMISSION: TO THE QUESTION ON THE SIZE OF SOURCES - Tsvyk, N. O. (Одеські астрономічні публікації, 2019)
There are debated the questions on size and properties of sources of Jupiter DAM radio emission (JRE). The evolution and the parameters of the sources in the DAM Io-B-storm of October 30, 2008, consisting of a large number of S-bursts, and interspersed with L-bursts and N-bursts, are analyzed in detail. It is shown that S-bursts in this storm are most likely to occur in the northern hemisphere of Jupiter at heights (0–0.2)R j and at longitudes λ IIIs = (195–220) o (when Jupiter is deployed to the observer CML = λ III = 130–160 o ). The onset of the Io-B-storm is associated with sources at high altitudes, and over time the sources drop down to Jupiter (as the observed S-burst frequencies increase with time). The possibility of the appearance of L- and N-bursts on the background of S-bursts is discussed. L-bursts can arise from the southern hemisphere of Jupiter, at a height of 0.2R j . And N-bursts can most likely be located in the northern hemisphere at λ IIIs = 66 o at a height of 0.2R j . Using the spectral data on the JRE from 30.10.08, the sizes (thickness and length) of filament-like sources of JRE - electron beams were determined, and the parameters of the MHD (Alfven) waves that activating the JRE bursts. It is shown that the L-radiation sources most likely appear to be thin filaments elongated to magnetic field lines, with a thickness of more then 10 km, and up to 2000 km in length. And the sources of S-radiation look like links with filament-like emissions less than 1 km thick (10–100 strands in a bundle) and up to 300 km in length flying at a speed of (0.05–0.1) c away from Jupiter . The observed A-wave velocities are 2–3 times slower than the A-wave velocity predicted theoretically (about 0.001 c, in light velocity units). Frequency (0.2–1 MHz) and temporal (up to 1 min) diffraction modulation of "lanes" confirms the size of the S-sources less than 200 km. Conclusions are made about the theoretical prerequisites for the appearance of S-bursts with observed parameters. Estimates of the radiation intensity of S-sources indicate an addi- tional increase in the radiation of the source near the generation region; this indicates a non-homogeneous structure of the environment in the active regions of the Jupiter magnetosphere. The thin transverse structure of the S-sources can be explained by the mechanism of plasmas fluctuations with periods of τ = τ ea = 10 ms, and with the peculiarities of the bunches of plasma clots that lead to electron leakage and to the emission of plasma plaits. The observed deceleration of the MHD wave velocities can be explained by the influence of the Io – Jupiter flow tube.